2019
DOI: 10.1002/hyp.13593
|View full text |Cite
|
Sign up to set email alerts
|

Changes in event‐based streamflow magnitude and timing after suburban development with infiltration‐based stormwater management

Abstract: Green stormwater infrastructure implementation in urban watersheds has outpaced our understanding of practice effectiveness on streamflow response to precipitation events. Long-term monitoring of experimental suburban watersheds in Clarksburg, Maryland, USA, provided an opportunity to examine changes in event-based streamflow metrics in two treatment watersheds that transitioned from agriculture to suburban development with a high density of infiltration-focused stormwater control measures (SCMs). Urban Treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 32 publications
1
45
1
Order By: Relevance
“…We feel that it is still important to continue to evaluate hydrologic metrics where possible based on subdaily flow data, and potentially even individual runoff events. Recent work by Hopkins et al (2019) demonstrates how analysis of individual runoff events is yielding unique insight into hydrological responses from watersheds with differing SCM strategies. In the future, analysis of subdaily flow patterns in concert with high-temporalresolution information on watershed hydrological dynamics such as dry weather flows could yield important insights into more specific mechanisms by which urbanization is altering hydrology.…”
Section: Methodological Insights For Future Study Of Flow Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…We feel that it is still important to continue to evaluate hydrologic metrics where possible based on subdaily flow data, and potentially even individual runoff events. Recent work by Hopkins et al (2019) demonstrates how analysis of individual runoff events is yielding unique insight into hydrological responses from watersheds with differing SCM strategies. In the future, analysis of subdaily flow patterns in concert with high-temporalresolution information on watershed hydrological dynamics such as dry weather flows could yield important insights into more specific mechanisms by which urbanization is altering hydrology.…”
Section: Methodological Insights For Future Study Of Flow Regimesmentioning
confidence: 99%
“…Detention-based storm water management decreases peak flows in some cases, but it also can drive more extended periods of high streamflow. Infiltration or retention-based storm water management decreased peak flows and increased baseflow in some cases (Hopkins et al, 2019;Loperfido et al, 2014) but had little detectable effect on hydrograph characteristics in others (Jefferson et al, 2017). A recent comparison of hydrograph characteristics across watersheds of varying SCM density in the Baltimore-Washington metro area of the United States did find decreases in peak runoff and decreasing streamflow variability with increased density of SCMs (Pennino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study indicates that incoming sediment has high impact on the water quality volume; it is suggested that filtering/infiltration stormwater control measures (e.g., bioretention, sand filter, infiltration trenches, etc.) be employed upstream of stormwater ponds, as filtering devices reduce the incoming sediment and infiltration devices reduce sediment and runoff volume altogether ( 2 ). Overall, further research is required to quantify the benefit of this proposed improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, related research indicates that although stormwater detention ponds are effective in controlling runoff peak flows on the site scale, they often do not make significant improvement on the watershed level. To improve this, it is recommended to modify the pond outlets with restriction to provide ''extended detention'' or to use runoff volumebased control (instead of the peak flow control (1,2). One typical outlet restriction is to provide the lowest orifice (also known as ''low flow orifice'' in local engineering jargons) near the pond bottom to provide ''extended detention'' in ponds.…”
mentioning
confidence: 99%
“…Bioretention cells reduce peak flows and runoff volumes, at both the site and neighborhood scale (Avellaneda et al, 2017; Jarden et al, 2016; Winston et al, 2016). In paired watershed studies, distributed SCMs, which use harvest and infiltration approaches, improve stream hydrology when compared to centralized, detention‐based SCMs, although neither approach yields a flow regime equivalent to undeveloped watersheds (e.g., Hopkins et al, 2019). Whatever approach is used, restoration or preservation of the flow regime is a key element in maintaining the ecological integrity of urban streams (Poff et al, 1997).…”
Section: Introductionmentioning
confidence: 99%